2020
DOI: 10.1007/s00068-020-01460-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors with the strongest prognostic value associated with in-hospital mortality rate among patients operated for acute subdural and epidural hematoma

Abstract: Introduction Traumatic brain injury (TBI) still remains a serious health problem and is called a “silent epidemic”. Each year in Europe 262 per 100,000 individuals suffer from TBI. The most common consequence of severe head injuries include acute subdural (SDH) and epidural hematomas (EDH), which usually require immediate surgically treatment. The aim of our study is to identify factors which have the strongest prognostic value in relation to in-hospital mortality rate among of patients undergoing surgery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 70 publications
(92 reference statements)
2
13
0
1
Order By: Relevance
“…Computer tomography scan after TBI provides an objective assessment of a structural damage to the brain and can help in predicting prognosis (3,19). There is strong evidence that greater midline shift and the thickness of hematoma are associated with a higher mortality rate, our results also confi rm that (30,31,32).…”
Section: Computer Tomography Scan Characteristicssupporting
confidence: 73%
See 3 more Smart Citations
“…Computer tomography scan after TBI provides an objective assessment of a structural damage to the brain and can help in predicting prognosis (3,19). There is strong evidence that greater midline shift and the thickness of hematoma are associated with a higher mortality rate, our results also confi rm that (30,31,32).…”
Section: Computer Tomography Scan Characteristicssupporting
confidence: 73%
“…The Glasgow Coma Scale (GCS) is the most common scale for assessing the patient's state of consciousness after a head injury. The age followed by the GCS motor score and the pupil response are most powerful independent prognostic factor after TBI (5,15) especially with extra-axial hematomas (3,14). In both groups GCS score was associated with in-hospital mortality with a statistically signifi cant difference.…”
Section: Physiological Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The use of illicit drugs and alcohol has been assessed in association with TBI, and a previously published literature review reported that nearly twothirds of TBI patients have a history of previous or current substance abuse, while approximately half are intoxicated at the time of injury [8]. It is important to note that drug and alcohol intoxication at the time of injury has mixed results within the literature in relation to mortality rates, but is associated with decreased functional outcomes [3,[9][10][11]. Furthermore, history of substance abuse has been correlated with TBI outcomes, including mortality, long-term functional outcomes, and other complications [10].…”
Section: Introductionmentioning
confidence: 99%